2019
DOI: 10.1007/s12298-019-00676-2
|View full text |Cite
|
Sign up to set email alerts
|

Salinity stress in cotton: effects, mechanism of tolerance and its management strategies

Abstract: Cotton is classified as moderately salt tolerant crop with salinity threshold level of 7.7 dS m-1. Salinity is a serious threat for cotton growth, yield and fiber quality. The sensitivity to salt stress depends upon growth stage and type of salt. Understanding of cotton response to salinity, its resistance mechanism and looking into management techniques may assist in formulating strategies to improve cotton performance under saline condition. The studies have showed that germination, emergence and seedling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 100 publications
3
90
0
2
Order By: Relevance
“…About 7% of the total global land area is affected by the detrimental effects of salinity [4]. It has also been projected that 20% of the total cultivable land and 33% of the irrigated agricultural land are affected by salt, an area that increases at an alarming rate of 10% annually, equating to a 2.0% and 3.3% increase per annum, respectively [5,6]. In China, approximately 4.88% of the total available land is affected by salinity [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 7% of the total global land area is affected by the detrimental effects of salinity [4]. It has also been projected that 20% of the total cultivable land and 33% of the irrigated agricultural land are affected by salt, an area that increases at an alarming rate of 10% annually, equating to a 2.0% and 3.3% increase per annum, respectively [5,6]. In China, approximately 4.88% of the total available land is affected by salinity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from antioxidants, the plant also accumulates various osmolytes, such as sugar, proteins, amino acids, and glycine betaine, for metabolic modification to overcome salt-induced lethal effects. Organic osmolytes are deposited within vacuoles of the cytoplasm to maintain osmotic adjustment, protect cell membranes, and denature protein by retaining the cell turgor [6,22]. It has been reported that plants with an improved antioxidant defense system, stronger metabolism of organic osmolytes, and higher accumulation of essential mineral nutrients display better salt tolerance [23,24].The adaptation of plants to salt stress may result in several aspects that function at the ionic, morphological, physiological, biochemical, and genetic levels [25,26].…”
mentioning
confidence: 99%
“…Accumulation of SuSy under abiotic stress has been found in several plants, especially in roots [35][36][37] . SuSy is not only involved in osmotic regulation of plants, but also functions at a branch point to allocate sucrose to either cell wall biosynthesis or glycolysis [38] .…”
Section: Analysis Of Salt Stress Resistant Dapsmentioning
confidence: 99%
“…Salinity stress is one of the most serious factors limiting plant growth and production. It has been estimated that more than 20% of irrigated land is suffering with high salinity, and the salinized land is becoming more widespread due to climate change and human input [ 1 ]. High concentrations of salts in the soil make it difficult for plants to take up water, and excessive salt intake can be toxic to plants, leading to failure in ion homeostasis and growth [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are about 35 million ha of land for cotton fields, and 75% of cotton fields suffer from salt stress [ 32 ]. Therefore, high salinity stress is a serious threat to cotton growth and production, especially at germination and seedling stages [ 1 ]. Understanding the genetic and epigenetic mechanism of cotton response to salinity may assist in developing strategies for improvements in salt tolerance of cotton.…”
Section: Introductionmentioning
confidence: 99%